Difference between revisions of "009B Sample Final 1, Problem 4"
Jump to navigation
Jump to search
(Created page with "<span class="exam"> Compute the following integrals. <span class="exam">a) <math>\int e^x(x+\sin(e^x))~dx</math> <span class="exam">b) <math>\int \frac{2x^2+1}{2x^2+x}~dx</m...") |
|||
Line 1: | Line 1: | ||
<span class="exam"> Compute the following integrals. | <span class="exam"> Compute the following integrals. | ||
− | <span class="exam">a) <math>\int e^x(x+\sin(e^x))~dx</math> | + | ::<span class="exam">a) <math>\int e^x(x+\sin(e^x))~dx</math> |
− | <span class="exam">b) <math>\int \frac{2x^2+1}{2x^2+x}~dx</math> | + | ::<span class="exam">b) <math>\int \frac{2x^2+1}{2x^2+x}~dx</math> |
− | <span class="exam">c) <math>\int \sin^3x~dx</math> | + | ::<span class="exam">c) <math>\int \sin^3x~dx</math> |
{| class="mw-collapsible mw-collapsed" style = "text-align:left;" | {| class="mw-collapsible mw-collapsed" style = "text-align:left;" | ||
Line 12: | Line 12: | ||
|Recall: | |Recall: | ||
|- | |- | ||
− | |'''1.''' Integration by parts tells us that <math style="vertical-align: -12px">\int u~dv=uv-\int v~du</math> | + | | |
+ | ::'''1.''' Integration by parts tells us that <math style="vertical-align: -12px">\int u~dv=uv-\int v~du.</math> | ||
|- | |- | ||
− | |'''2.''' Through partial fraction decomposition, we can write the fraction <math style="vertical-align: -18px">\frac{1}{(x+1)(x+2)}=\frac{A}{x+1}+\frac{B}{x+2}</math> | + | | |
+ | ::'''2.''' Through partial fraction decomposition, we can write the fraction <math style="vertical-align: -18px">\frac{1}{(x+1)(x+2)}=\frac{A}{x+1}+\frac{B}{x+2}</math> | ||
|- | |- | ||
− | |'''3.''' We have the Pythagorean identity <math style="vertical-align: -5px">\sin^2(x)=1-\cos^2(x)</math> | + | | |
+ | :::for some constants <math style="vertical-align: -4px">A,B.</math> | ||
+ | |- | ||
+ | | | ||
+ | ::'''3.''' We have the Pythagorean identity <math style="vertical-align: -5px">\sin^2(x)=1-\cos^2(x).</math> | ||
|} | |} | ||
Line 33: | Line 39: | ||
|Now, for the first integral on the right hand side of the last equation, we use integration by parts. | |Now, for the first integral on the right hand side of the last equation, we use integration by parts. | ||
|- | |- | ||
− | |Let <math style="vertical-align: 0px">u=x</math> and <math style="vertical-align: 0px">dv=e^xdx</math> | + | |Let <math style="vertical-align: 0px">u=x</math> and <math style="vertical-align: 0px">dv=e^xdx.</math> Then, <math style="vertical-align: 0px">du=dx</math> and <math style="vertical-align: 0px">v=e^x.</math> |
|- | |- | ||
|So, we have | |So, we have | ||
Line 50: | Line 56: | ||
|Now, for the one remaining integral, we use <math style="vertical-align: 0px">u</math>-substitution. | |Now, for the one remaining integral, we use <math style="vertical-align: 0px">u</math>-substitution. | ||
|- | |- | ||
− | |Let <math style="vertical-align: 0px">u=e^x</math> | + | |Let <math style="vertical-align: 0px">u=e^x.</math> Then, <math style="vertical-align: 0px">du=e^xdx.</math> |
|- | |- | ||
|So, we have | |So, we have | ||
Line 88: | Line 94: | ||
|Now, we need to use partial fraction decomposition for the second integral. | |Now, we need to use partial fraction decomposition for the second integral. | ||
|- | |- | ||
− | |Since <math style="vertical-align: -5px">2x^2+x=x(2x+1)</math> | + | |Since <math style="vertical-align: -5px">2x^2+x=x(2x+1),</math> we let |
+ | |- | ||
+ | | | ||
+ | ::<math>\frac{1-x}{2x^2+x}=\frac{A}{x}+\frac{B}{2x+1}.</math> | ||
+ | |- | ||
+ | |Multiplying both sides of the last equation by <math style="vertical-align: -5px">x(2x+1),</math> we get | ||
+ | |- | ||
+ | | | ||
+ | ::<math style="vertical-align: -5px">1-x=A(2x+1)+Bx.</math> | ||
|- | |- | ||
− | | | + | |If we let <math style="vertical-align: 0px">x=0</math>, the last equation becomes |
|- | |- | ||
− | | | + | | |
+ | ::<math style="vertical-align: -1px">1=A.</math> | ||
|- | |- | ||
− | |If we let <math style="vertical-align: | + | |If we let <math style="vertical-align: -14px">x=-\frac{1}{2},</math> then we get  <math style="vertical-align: -13px">\frac{3}{2}=-\frac{1}{2}\,B.</math> Thus, |
|- | |- | ||
− | | | + | | |
+ | ::<math style="vertical-align: 0px">B=-3.</math> | ||
|- | |- | ||
− | |So, in summation, we have  <math>\frac{1-x}{2x^2+x}=\frac{1}{x}+\frac{-3}{2x+1}</math> | + | |So, in summation, we have  |
+ | |- | ||
+ | | | ||
+ | ::<math>\frac{1-x}{2x^2+x}=\frac{1}{x}+\frac{-3}{2x+1}.</math> | ||
|} | |} | ||
Line 119: | Line 138: | ||
|For the final remaining integral, we use <math style="vertical-align: 0px">u</math>-substitution. | |For the final remaining integral, we use <math style="vertical-align: 0px">u</math>-substitution. | ||
|- | |- | ||
− | |Let <math style="vertical-align: -2px">u=2x+1</math> | + | |Let <math style="vertical-align: -2px">u=2x+1.</math> Then, <math style="vertical-align: 0px">du=2\,dx</math> and  <math style="vertical-align: -14px">\frac{du}{2}=dx.</math> |
|- | |- | ||
|Thus, our final integral becomes | |Thus, our final integral becomes | ||
Line 143: | Line 162: | ||
!Step 1: | !Step 1: | ||
|- | |- | ||
− | |First, we write <math style="vertical-align: -13px">\int\sin^3x~dx=\int \sin^2 x \sin x~dx</math> | + | |First, we write <math style="vertical-align: -13px">\int\sin^3x~dx=\int \sin^2 x \sin x~dx.</math> |
|- | |- | ||
− | |Using the identity <math style="vertical-align: -2px">\sin^2x+\cos^2x=1</math>, we get <math style="vertical-align: -1px">\sin^2x=1-\cos^2x</math> | + | |Using the identity <math style="vertical-align: -2px">\sin^2x+\cos^2x=1</math>, we get |
+ | |- | ||
+ | | | ||
+ | ::<math style="vertical-align: -1px">\sin^2x=1-\cos^2x.</math> | ||
|- | |- | ||
|If we use this identity, we have | |If we use this identity, we have | ||
|- | |- | ||
− | | <math style="vertical-align: -13px">\int\sin^3x~dx=\int (1-\cos^2x)\sin x~dx</math> | + | | <math style="vertical-align: -13px">\int\sin^3x~dx=\int (1-\cos^2x)\sin x~dx.</math> |
− | |||
− | |||
|} | |} | ||
Line 157: | Line 177: | ||
!Step 2: | !Step 2: | ||
|- | |- | ||
− | |Now, we proceed by <math>u</math>-substitution. Let <math>u=\cos x</math> | + | |Now, we proceed by <math>u</math>-substitution. Let <math>u=\cos x.</math> Then, <math style="vertical-align: -1px">du=-\sin x dx.</math> |
|- | |- | ||
|So we have | |So we have |
Revision as of 12:03, 18 April 2016
Compute the following integrals.
- a)
- b)
- c)
Foundations: |
---|
Recall: |
|
|
|
|
Solution:
(a)
Step 1: |
---|
We first distribute to get |
|
Now, for the first integral on the right hand side of the last equation, we use integration by parts. |
Let and Then, and |
So, we have |
|
Step 2: |
---|
Now, for the one remaining integral, we use -substitution. |
Let Then, |
So, we have |
|
(b)
Step 1: |
---|
First, we add and subtract from the numerator. |
So, we have |
|
Step 2: |
---|
Now, we need to use partial fraction decomposition for the second integral. |
Since we let |
|
Multiplying both sides of the last equation by we get |
|
If we let , the last equation becomes |
|
If we let then we get Thus, |
|
So, in summation, we have |
|
Step 3: |
---|
If we plug in the last equation from Step 2 into our final integral in Step 1, we have |
|
Step 4: |
---|
For the final remaining integral, we use -substitution. |
Let Then, and |
Thus, our final integral becomes |
|
Therefore, the final answer is |
|
(c)
Step 1: |
---|
First, we write |
Using the identity , we get |
|
If we use this identity, we have |
Step 2: |
---|
Now, we proceed by -substitution. Let Then, |
So we have |
|
Final Answer: |
---|
(a) |
(b) |
(c) |